The Diversion’s Application for Juvenile Offenders - Novi Wulandari; Ida Keumala Jeumpa; M. Yakub Aiyub Kadir (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
The resolution of juvenile cases in Indonesia requires a restorative justice approach as outlined in Law Number 11 of 2012 on the Juvenile Criminal Justice System (UUSPPA). However, Article 7, paragraph (2) restricts diversion to crimes punishable by less than seven years, excluding repeat offenders. This presents challenges for minors involved in serious crimes, such as rape, leading to concerns over child protection and fairness in the justice system. The implementation of diversion in the Syari’ah Court follows national juvenile justice protocols but faces challenges, especially in maintaining consistency across law enforcement agencies and regions. The study employs an empirical juridical approach and explores the challenges of implementing diversion in the Aceh Sharia Court. Findings reveal that diversion efforts are often inconsistent and rely on the discretion of authorities. Although the Child Criminal Justice System Law mandates diversion for cases involving crimes with sentences under seven years and non-recidivists, its actual application varies. For instance, rape cases between 2020 and 2023 show that some were excluded from diversion due to their serious nature, while others still pursued diversion despite the potential for sentences exceeding seven years.